A brain-penetrant bispecific antibody lowers oligomeric alpha-synuclein and activates microglia in a mouse model of alpha-synuclein pathology - Dag Sehlin; Sahar Roshanbin; Olof Zachrisson; Martin Ingelsson; Stina Syvänen (Neurotherapeutics)
Parkinson's disease (PD) is characterized by a progressive loss of dopaminergic neurons, linked to aggregation of alpha-synuclein (αSYN) into Lewy bodies. Current treatments are symptomatic and do not halt or reverse the neurodegeneration. Immunotherapy targeting aggregated αSYN shows potential, but therapeutic efficacy is limited by poor brain penetration of antibodies. We developed a bispecific antibody, RmAb38E2-scFv8D3, based on αSYN oligomer selective RmAb38E2 fused to a transferrin receptor (TfR)-binding domain to enhance brain delivery. Both RmAb38E2 and RmAb38E2-scFv8D3 showed higher affinity for αSYN oligomers than for monomers or fibrils. In vivo, RmAb38E2-scFv8D3 exhibited higher brain and lower blood concentrations compared to RmAb38E2, suggesting a better brain uptake and reduced peripheral exposure for the bispecific antibody. Treatment over five days of 3–4 months old transgenic L61 mice, which overexpress human αSYN, with three doses of RmAb38E2-scFv8D3 reduced brain αSYN oligomer levels and increased microglial activation, as indicated by elevated soluble TREM2 levels. Treatment with the monospecific RmAb38E2, however, showed no significant effect compared to PBS. This study demonstrates that TfR-mediated delivery enhances the therapeutic potential of αSYN-targeted immunotherapy by resulting in a higher concentration and a more uniform distribution of antibodies in the brain. The use of bispecific antibodies offers a promising strategy to improve the efficacy of antibody therapies in PD and other α-synucleinopathies.